Determinant and Countermeasures Student Deviant Behavior in Public Junior High School 1 Terisi, Indramayu District - Risnaedi, Astri Sulistiani; Rachman, Maman; Murwatiningsih, Murwatiningsih (JESS (Journal of Educational Social Studies), 2018)
Education is seen as one aspect that plays an important role in shaping the character for future generations. School is one of the educational environment. At school, students receive an academic and non-academic education so that they behave well in accordance with school rules and norms. However, in reality in school, there are still students who behave deviant. The purpose of this study is to analyze the form of deviant behavior of students, factors causing students to behave deviant and the prevention of teachers in schools in preventing and overcoming deviant behavior in students. This study used a qualitative approach to case studies by examining the behavior of deviant students in one of the schools located in Indramayu District. The data were collected from 14 informants, consisting of principals, Guidance and Counseling (BK) teachers, two Social Sciences (IPS) teachers, Civics teachers, and nine students. The data collecting by observation is done by observation of the students, the interview is done by dialogue directly by involving the school also some students and parents and documentation by using data contained in school. Data analysis uses data interaction. From the results of data processing obtained research results that show that there are deviant behaviors performed by a small number of students, in the form of a brawl, ditching, and alcohol/illegal drugs. The student's deviant behavior is caused by incomplete socialization factor in the form of incomplete family and unharmonious family, and deviant subcultural factors that influence the school environment, peer influence, and mass media influence. The prevention done by teachers during this time includes preventive, repressive, and curative action.